Ultrasonication on Collagen Yield, Physiochemical and Structural Properties from Seabass (Lates Calcarifer) Scales as Affected by Pretreatment and Extraction Conditions - Bavisetty, Sri Charan Bindu; Karnjanapratum, Supatra; Dave, Jaydeep; Purba, Daniel Tua; Kudre, Tanaji; Maser, Wahyu Haryati; Maiyah, Nur; Kingwascharapong, Passakorn; Ali, Ali Muhammed Moula (My University, 2024)
This research explored the use of ultrasound as a pretreatment and extraction assisted process for extraction of collagen from seabass scales. Both acid-soluble (AC) and pepsin-soluble collagens (PC) were extracted with ultrasonication at different extraction times (24 and 48 h). Ultrasound pretreatment (PU) and ultrasound-assisted extraction (UE) notably improved AC extraction yields over 48 hours, registering 2.12% and 4.62%, respectively. The highest yield for PC, 21.85%, was achieved with 48 hours of ultrasound assisted extraction. Protein analysis verified the extracted collagens as type I, indicated by the presence of specific α and β chains. Further, FTIR spectra confirmed collagen's presence in all samples through distinct amide band peaks. Interestingly, ultrasound processes marginally reduced AC's thermal stability while boosting PC's thermal stability, especially when combined with pepsin treatment. Moreover, CD spectroscopy showed the preserved native structure of collagen across all samples. The ultrasound method increased collagen extraction yields and retained its structural integrity. These outcomes are pivotal for advancing collagen extraction methods in the biomedical and food sectors.
Keywords: Collagen; Molecular characterization; Physicochemical properties; Seabass scales; Ultrasonication